Analysis of Items with Item Response Theory (IRT) Approach on Final Assessment for Al-Quran Hadith Subjects - Syafii, Ahmad; Haryanto, Haryanto; Ahmad, Iqbal Faza; Fauziah, Arifah (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
Measurement in the field of education, especially the teaching and learning process can be done with measuring tools in the form of tests and non-tests. Islamic Religious Education is considered the same as other subjects. to realize student success is also measured through evaluation, which is a systematic process to obtain information about the effectiveness of teaching and learning activities. In addition, it can also assist teachers in achieving learning objectives and describe student achievement in accordance with predetermined criteria. This study aims to analyze the Year-End Assessment of MAN 2 Bantul for the 2020/2021 academic year consisting of 25 multiple-choice questions. The items analyzed in the report have a total number of responses of 265 students. Item analysis using analysis with modern test theory ( Item Response Theory ). The results showed that the results of the model fit test showed that the instrument fit on the 2 PL model (Logistics parameter) with the lowest AIC value, namely 4874.85. The results of the parameter analysis of the level of difficulty indicate that there are 4 questions that are categorized as very easy, 4 easy questions, 15 moderate questions, 1 difficult question, and 1 very difficult question. This shows that the distribution of the difficulty level parameters is quite balanced. The results of the analysis of the different power parameters show that there are 23 good questions, 1 fairly good question, and 1 bad question. This shows that the different power level parameters are quite good. The results of the estimation of students' abilities with the MLE estimator showed that there were no students who had abilities below -4. There are 15 students with abilities above 2.00. There are 165 students who fall into the good category (ability -2 to 2 and 9 students who have abilities below -2. Based on the plot of the information function, it can be concluded that the optimal test if given to individuals with low abilities is around -1.2. Accurate questions to measure students' abilities with a range of -2.5 to 1.2.